1997
DOI: 10.2172/554804
|View full text |Cite
|
Sign up to set email alerts
|

Tritium monitoring in groundwater and evaluation of model predictions for the Hanford Site 200 Area Effluent Treatment Facility

Abstract: This report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, makes any warranty, exprcss or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific commercial product, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 9 publications
(17 reference statements)
2
41
1
Order By: Relevance
“…Well 699-48-77A was f~st affected by discharges in August of 1996. Although this well is fi,u-thestaway fi-omthe facility of the three "proximal" SALDS wells, subsurface geologic factors allowed the effluent to reach this well before any others (see Barnett et al 1997). This well produced a maximum tritium activity during FY 2000 of 150,000 pCi/L (October 1999), which is 10,000 pCi/L higher than the FY 1999 maximum.…”
Section: Results Of Groundwater Analyses For Ilitiummentioning
confidence: 95%
See 2 more Smart Citations
“…Well 699-48-77A was f~st affected by discharges in August of 1996. Although this well is fi,u-thestaway fi-omthe facility of the three "proximal" SALDS wells, subsurface geologic factors allowed the effluent to reach this well before any others (see Barnett et al 1997). This well produced a maximum tritium activity during FY 2000 of 150,000 pCi/L (October 1999), which is 10,000 pCi/L higher than the FY 1999 maximum.…”
Section: Results Of Groundwater Analyses For Ilitiummentioning
confidence: 95%
“…The current numerical groundwater/tritiurn model (Cole and Wurstner in Barnett et al 1997) indicated that tritium would first arrive at the 200 West Area northern boundary in 2000, and would then be detectable in as many as three wells along this boundary. In this model, well 299-W7-3 is less than 100 m outside the area of the predicted plume, with wells 299-W7-5, 299-W7-6, and 299-W7-7 lying inside the 500 pCi/L portion (lowest practically detectable) portion of the plume.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples of local-scale modeling studies and investigations supported by a site-wide model include modeling studies described in Wood et al (1995Wood et al ( , 1996, Barnett et al (1997), and Bergeron and Wurstner (2000). A brief summary of each of these efforts and how a site-wide model was used in supporting the analysis is provided in the following sections.…”
Section: Appropriate Uses and Selected Examplesmentioning
confidence: 99%
“…For groundwater flow and saturated-zone transport of contaminants, an existing three-dimensional numerical model that has been developed for the Hanford Site unconfined Aquifer (Wurstner et al 1995;Barnett et al 1997;Cole et al 1997) was used. Predictions of groundwater flow in the unconfined aquifer focused on the response of the aquifer to the cessation of wastewater discharges from Hanford Site operations.…”
Section: Groundwater Transportmentioning
confidence: 99%